Types of Academic Motivation according to Self Determine for students of The College of Education for Women - رحيم عصفور خلود (Al-Adab Journal, 2018)
The current research aims to identify the types of academic motivation based on the theory of self-determine for fourth-grade students in the College of Education for women in addition to know the significance of differences in the mean scores of the students on a scale of academic motivation according to variables (scientific department, academic achievement, the desire to study in the department, expect to get a job within a specialization after graduation) . The research sample included 500 female students from the fourth grade of 50 students from each department were used to measure Ryan & Deci after that has been translated into Arabic and the definition of psychometric properties has indicated. That the results of research on the order of the types of motivation among a sample search from highest to lowest in a row was in the following order (Introjected regulation , to Know , to Accomplish , External regulation , Identified regulation , to Stimulate , Amotivation) . The results also indicated that the social service department has recorded the highest average in (to Know), The Department of Science of Quran has recorded the highest average in (to Accomplish), Department of History the highest average in (to Stimulate ) , department of science of Quran first record average in each of (Identified regulation and Introjected regulation) while the English department record the highest average in (External regulation) , and Department of History has record the highest average in (Amotivation) while English department has recorded the lowest average in (Amotivation ) . The results also indicated that there are differences in the types of motivation according to academic achievement (Good / Pad) in favor of a good achievement with the exception of Amotivation , it’s also found differences in the types of motivation on according to the desire to study the department ( desire / does not desire ) in favor of the desire except for the Amotivation was for does not desire , and found differences in the types of motivation based on future expectation to get a job within the specialization (expected / not expected) Except for the expected Amotivation for the benefit is not expected. Recommends that the current researcher the departments which recorded a low level of academic motivation, the need to review the educational programs and modified to work on raising the level of academic motivation.